2021
DOI: 10.1155/2021/3298515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Atmospheric Pressure Plasma Coupled with Resin-Containing and Xylitol-Containing Fluoride Varnishes on Enamel Erosion

Abstract: Purpose. Considering the suggested advantages of cold atmospheric plasma (CAP) in increasing the fluoride uptake by the enamel, this study aimed to assess enamel erosion following the application of helium CAP and two types of fluoride varnishes. Methods. The microhardness of 70 bovine enamel specimens was measured using a Vickers hardness tester. The specimens were randomly divided into 7 groups (n = 10): control, CAP (P), resin-containing fluoride varnish (RF), CAP + resin-containing fluoride varnish (PRF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…These results are consistent with the results of other studies [ 37 , 38 , 39 , 40 , 41 , 42 ] which have shown that varnishes containing sodium fluoride are effective in modifying the roughness of the enamel surface. Other studies that have used the AFM analysis technique [ 42 , 43 , 44 ] have found that the hardness of dental hard tissues decreases after the use of fluoride varnishes. Additionally, fluoride varnish is effective in reducing enamel demineralization [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the results of other studies [ 37 , 38 , 39 , 40 , 41 , 42 ] which have shown that varnishes containing sodium fluoride are effective in modifying the roughness of the enamel surface. Other studies that have used the AFM analysis technique [ 42 , 43 , 44 ] have found that the hardness of dental hard tissues decreases after the use of fluoride varnishes. Additionally, fluoride varnish is effective in reducing enamel demineralization [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Microhardness is usually related to materials' mechanical properties and is an essential property of dental materials associated with compressive strength and resistance to softening [ 10 ]. Low cost and being easy application may cause this method to be popular in evaluating dental erosion [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Kim et al showed that using a cold atmospheric plasma (CAP) device, the fluoride uptake and retention from a 1.23% acidulated P fluoride gel, along with the acid resistance, were improved on enamel specimens [ 10 ]. In 2021, Khoubrouypak et al [ 28 ] reported the effects of helium CAP on enamel erosion when testing two fluoride varnishes (Enamelast and FluoroDose), both having concentrations of 22600 ppm F. Based on the mechanisms reported in the literature regarding the improvement of fluoride varnishes’ efficiency by CAP, two assumptions were considered at the beginning, but only the second was assumed for their study. The first one was previously reported by Kim et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that for an argon plasma, the wettability of the dentin substrates increases, but with no differences in the contact angle values for different input powers or for treatments longer than 30 s. For the enamel surface, the contact angle values decreased from 24.0 ± 5.5° to 3.3 ± 1.0° after 30 s of plasma treatment. Based on the study results, Khoubrouypak et al concluded that the CAP treatment did not significantly increase the enamel erosion resistance, which was mainly assigned to the fluoride varnish application [ 28 ].…”
Section: Discussionmentioning
confidence: 99%